Word Order Affects Response Latency: Action Projection and the Timing of Responses to Question-word Questions. Issue 4 (21st April 2021) - Pekarek Doehler, Simona
ABSTRACT: This article explores the relation between word order and response latency, focusing on responses to question-word questions. Qualitative (multimodal) and quantitative analyses of naturally occurring conversations in French—where question-words can occur in initial, medial, or final position within the question—show that variation in word order affects the timing of responses. It is argued that this is so because word order provides a differential basis for action ascription, creating different temporal opportunities for projecting the recipient's next relevant action. The frequent occurrence of early responses to questions with an initial question-word, in particular, stresses the importance of the recognition point of an action under way for response timing and shows respondents' pervasive orientation to sequential progressivity. Findings highlight how lexico-syntactic trajectories of emergent turns, prior talk and actions, material and bodily features of interaction, and participants' shared expectations conspire in shaping the time-courses of action ascription and action projection.